2014
DOI: 10.1002/pssc.201400046
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of carbon impurity concentration in silicon epitaxial layers by luminescence activation using carbon ion implantation and electron irradiation

Abstract: The calibration curve for the carbon concentration in silicon epitaxial layers was obtained by photo‐luminescence spectroscopy after carbon ion implantation and electron irradiation. Low carbon concentrations on the order of 1014 atoms/cm3 affected properties such as the on‐resistance and carrier lifetime of insulated gate bipolar transistors (IGBTs). We focused on carbon impurities because interstitial carbon can form complexes, such as complexes of interstitial and substitutional carbon (Ci‐Cs) and of inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The only difference between Si-epi and Si-Cz samples is given by the oxygen trapping peak located at the maximum melt depth (~500 nm), which is only observed in the Si-CZ sample. The formation of this trapping peak might be due to the interaction of the in-diffused oxygen atoms with the excess point defects generated at the maximum melt depth [29] as well as with C impurities already present in the substrate (whose concentration is much higher in Si-CZ wafers compared to Si-epi ones [30]). In a final experiment, we investigated a set of three CZ samples ("HF-pretreat", "Native oxide" and "Thermal oxide", cf.…”
Section: Impurities Penetration Mechanismmentioning
confidence: 99%
“…The only difference between Si-epi and Si-Cz samples is given by the oxygen trapping peak located at the maximum melt depth (~500 nm), which is only observed in the Si-CZ sample. The formation of this trapping peak might be due to the interaction of the in-diffused oxygen atoms with the excess point defects generated at the maximum melt depth [29] as well as with C impurities already present in the substrate (whose concentration is much higher in Si-CZ wafers compared to Si-epi ones [30]). In a final experiment, we investigated a set of three CZ samples ("HF-pretreat", "Native oxide" and "Thermal oxide", cf.…”
Section: Impurities Penetration Mechanismmentioning
confidence: 99%
“…Defects, such as oxygen precipitates and vacancy‐light element complexes, form due to the interaction between these impurities and point defects during device processes, such as ion implantation, so that they would degrade carrier lifetime and increase C–E leakage current and on‐voltage of IGBTs. It has recently been reported that carbon‐related complexes, such as Ci‐Cs (G‐line) and Ci‐Oi (C‐line), decrease lifetime . Therefore, reducing carbon in the crystal has been required.…”
Section: Comment On Development Of Mcz‐si Crystals For Future Siliconmentioning
confidence: 99%
“…It has recently been reported that carbonrelated complexes, such as Ci-Cs (G-line) and Ci-Oi (C-line), decrease lifetime. [57][58][59] Therefore, reducing carbon in the crystal has been required. In addition, because high-voltage IGBTs for infrastructure applications of a power supply require high resistivity and high lifetime materials, FZ-Si crystals with neutron transmutation doping (NTD) are used.…”
Section: Future Researchmentioning
confidence: 99%
“…Interstitial oxygen and substitutional carbon in silicon show the greatest influence on the performance of silicon wafers, whereas other types of oxygen and carbon have no effect. Destructive methods, such as gas fusion analysis 2 , 3 , secondary ion mass spectrometry 4 , 5 , helium activation analysis 6 , and luminescence activation analysis 7 , are used to analyse the content of oxygen and carbon in silicon wafers. The result obtained is the total element content of oxygen and carbon rather than that of their real specific interstitial and substitutional forms bonded in silicon wafers.…”
Section: Introductionmentioning
confidence: 99%